Balancing national security and human rights protection in wartime policing strategies in Latvia, Lithuania, and Ukraine - Dzikas, Darius (Теоретичні питання юриспруденції і проблеми правозастосування: виклики ХХІ століття : тези доп. учасників X Міжнар. наук.-практ. конф. (Харків, 25 трав. 2025 р.), 2025)
In the current context of military conflicts, the issue of balancing national security and human rights protection is particularly important. Given the geopolitical challenges, Latvia, Lithuania and Ukraine are forced to adapt their police strategies to the realities of wartime, ensuring both public order and human rights. Studying their experience is extremely important for developing effective approaches to law enforcement in times of crisis. The purpose of the study is to provide a comprehensive analysis of wartime police strategies in Latvia, Lithuania and Ukraine aimed at maintaining national security and protecting human rights, as well as to assess the effectiveness of legal mechanisms for controlling the activities of law enforcement agencies. Methods. The study uses the comparative legal method and the method of systematic analysis. Applying these approaches allowed for a comprehensive analysis of the legal framework and practical aspects of police activity in wartime. The study found that Latvia, Lithuania, and Ukraine use different approaches to ensure national security, but all of them are focused on compliance with international human rights standards. It has been found that the effectiveness of police strategies largely depends on the existence of clearly defined legal mechanisms for controlling the activities of law enforcement agencies, as well as the level of public trust in the police. Key challenges are identified, including the risk of abuse of power during martial law and the need to improve accountability procedures.